Linking fungal–bacterial co-occurrences to soil ecosystem function. (June 2017) - de Menezes, Alexandre B; Richardson, Alan E; Thrall, Peter H
Highlights: Fungi and bacteria interact in soil, likely affecting their ecosystem function. Correlation network analysis is a powerful tool to characterise F:B interactions. F:B co-occurrences should be linked to soil properties and processes. Co-occurrence-soil process linkages will improve ecosystem modelling and prediction. Co-occurring F:B will be targets for mechanistic characterisation of interactions. Abstract : Fungi and bacteria are major players in soil biogeochemical cycles, however, most studies linking soil processes to microbial function ignore the potential role of interactions between these groups. A small number of studies have used correlation network analyses to investigate fungal–bacterial co-occurrences in soil, and revealed differences, as well as overlaps, in the ecosystem roles of these groups. These results contradict the view that fungi and bacteria are two distinct functional groups which can be studied in isolation. A more comprehensive understanding of the interplay between soil properties, biogeochemical cycles and the interactions between fungi and bacteria will be an important step towards improving the prediction and management of soil ecosystem services.